(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
VANET is a type of Ad hoc network that enables the communication between vehicles and roadside units. It provides a broad range of applications, such as blind crossing, accident avoidance, protection, interactive route planning, traffic situation monitoring in real-time, etc. These applications are required to be very secure to achieve a reliable service and provide safety for drivers. This paper sheds light on three different types of attacks (Sybil Attack, Jamming Attack, Timing Attack) that can critically affect the vehicular ad hoc network environment. Furthermore, we present techniques that can overcome these attacks.